ANALISIS PENGARUH PROGRAM TVET TERHADAP PRODUKTIVITAS PEKERJA DENGAN KOMPETENSI SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN MANUFAKTUR OTOMOTIF PT. XYZ) - Radja Haikal, Al Razi; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze the effect of impact of Technical and Vocational Education and Training (TVET) program on worker’s workplace productivity, with competency as a moderating variable. This study uses TVET as the independent variable, productivity as the dependent variable, and competency as the moderating variable. The population of this study consists of all contract employees in the Assembly department of PT. XYZ who were recruited from November 2021 to March 2023, totaling 100 people. This study uses the entire population as the sample or utilizes a saturated sample. The data used in this research were obtained through a questionnaire method and tested and analyzed using SmartPLS 4.0 software. The results of the study indicate that participation in the TVET program has a positive and significant impact on an individual's workplace productivity. Additionally, it was found that competence mastery can moderate by strengthening the relationship between participation in the TVET program and workplace productivity